Anticipatory Action Works: Moving from crisis response to risk management - Wogderes, Abiy (World Food Programme, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025